Action Learning as a Human Resource Development Resource to Realize Collective Leadership - Joseph A. Raelin (Human Resource Development Review, 2021)
Action learning has been used as a potential resource of human resource development for adopting collective leadership. The word potential is noteworthy because it is not necessarily the conventional purpose of action learning when adopted as a human resource development tool. It is primarily used as a form of work-based learning. However, its components can be aptly constituted for the former purpose; in fact, action learning may be one of the best HRD methods to prepare participants for collective leadership in the organization.
Keywords: I21; M10; M12; M53; 330; action learning; collective leadership; leaderful practice; coaching